2013
DOI: 10.1503/jpn.120160
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind optimization of subcallosal cingulate deep brain stimulation for treatment-resistant depression: a pilot study

Abstract: IntroductionDeep brain stimulation (DBS) has recently emerged as a viable option for treatment-resistant depression (TRD). Among several neuroanatomical targets (subcallosal cingulate, nucleus accumbens, ventral capsule/ventral striatum, inferior thalamic peduncle and habenula), 1 DBS of the subcallosal cingulate (SCC) has been the most investigated. Four open-label studies of SCC-DBS involving a total of 66 patients with TRD (major depressive disorder and bipolar depression) showed efficacy and safety.2-7 Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 30 publications
2
46
0
2
Order By: Relevance
“…Ten publications from nine studies met inclusion criteria (Bergfeld et al., ; Dougherty et al., ; Kubu et al., ; Merkl et al., ; Holtzheimer et al., , ; Puigdemont et al., ; Ramasubbu, Anderson, Haffenden, Chavda, & Kiss, ; Schlaepfer, Bewernick, Braeuer, & Coenen, ; Fenoy et al., ). Table gives details of those studies that were excluded at the full‐text level.…”
Section: Resultsmentioning
confidence: 99%
“…Ten publications from nine studies met inclusion criteria (Bergfeld et al., ; Dougherty et al., ; Kubu et al., ; Merkl et al., ; Holtzheimer et al., , ; Puigdemont et al., ; Ramasubbu, Anderson, Haffenden, Chavda, & Kiss, ; Schlaepfer, Bewernick, Braeuer, & Coenen, ; Fenoy et al., ). Table gives details of those studies that were excluded at the full‐text level.…”
Section: Resultsmentioning
confidence: 99%
“…The long-term response rate for SCC DBS was approximately 60% (94). In addition to appropriate electrode placement, programming parameters within this node have not been fully explored (95) and optimized (96). Future trials, such as the ongoing multi- site randomized control trial (BROADEN), may potentially utilize parameters described above to optimize treatment delivery.…”
Section: Tsmentioning
confidence: 99%
“…DBS studies targeting the SCC (21), internal capsule (97), and the reward circuitry (28, 101) have shown efficacy in not only severe unipolar depression, but also in individuals with bipolar disorder that were in an extended depressive episode (88). It is also clear that efficacy will increase when programming settings (96), the lead position in relation to the relevant circuitry (106), and the exact microstructural targets of modulation (93) are optimized. Ultimately, the DBS target choice for an individual's depression may be selected using the nature of the depressive symptoms (91) coupled with the side-effect profile and relevant comorbidities (107).…”
Section: Tsmentioning
confidence: 99%
“…More recent studies have begun to investigate the relationship between stimulus parameters and clinical efficacy. A small double blind pilot study [74] ( n =4) randomly changed frequency and pulse widths weekly in TRD patients who underwent DBS (aged 46–56). They found that longer pulse widths (270–450 μs) were associated with more robust antidepressant effects.…”
Section: Introductionmentioning
confidence: 99%